2010
DOI: 10.2169/internalmedicine.49.2191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory Impedance in Asthma and COPD by an Impulse Oscillation System

Abstract: Objective The purpose of this study was to clarify the differences in physiological properties of the airways between asthma and COPD using an impulse oscillation system (IOS). Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 29 publications
14
71
0
1
Order By: Relevance
“…Impedance and impedance entropy parameters in healthy subjects and patients with asthma In line with previous studies [27,28], we found significant increases in R5-R20 and AX, and to a lesser extent R20, in patients with severe asthma compared with healthy controls, suggesting that the baseline level of airway narrowing, and the accompanying heterogeneity of narrowing and closure, are increased in patients with severe asthma. We were unable to demonstrate a difference in these parameters between patients with severe asthma established on maintenance oral corticosteroids (GINA treatment step 5) and patients on high-dose inhaled corticosteroids (GINA treatment step 4), suggesting that these processes may be resistant to corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Impedance and impedance entropy parameters in healthy subjects and patients with asthma In line with previous studies [27,28], we found significant increases in R5-R20 and AX, and to a lesser extent R20, in patients with severe asthma compared with healthy controls, suggesting that the baseline level of airway narrowing, and the accompanying heterogeneity of narrowing and closure, are increased in patients with severe asthma. We were unable to demonstrate a difference in these parameters between patients with severe asthma established on maintenance oral corticosteroids (GINA treatment step 5) and patients on high-dose inhaled corticosteroids (GINA treatment step 4), suggesting that these processes may be resistant to corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the criterion of MEF50/MEF25, as a marker of small airway disease, can only be used in younger populations, whereas for older populations, the single criterion of MEF50/MEF25 does not appear to be sufficient for diagnosing the presence of small airway disease. Further measurements such as the closing volume test and respiratory resistance test using the impulse oscillation system, are also required to evaluate the function of the small airways (25,26). Moreover, in the present study, since there was no difference in the MEF50/MEF25 between smokers and never-smokers, MEF50/MEF25 was not confirmed to be a useful marker for cigarette smoke-induced airway damage.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, in general, R5 only moderately correlates with FEV1 in asthma and COPD (12,13). R5 is higher in patients with COPD than in healthy controls, but not in those with asthma (12,14).…”
Section: Rrsmentioning
confidence: 85%